EVALUASI KESESUAIAN LAHAN PERTANIAN UNTUK TANAMAN JAGUNG DI KECAMATAN KUALUH HILIR, LABUHAN BATU UTARA, SUMATERA UTARA - Manalu, Febbry Vebilola; Novira, Nina; Siahaan, Hana Margaretha; Fortunata, Lisna Anggia; Rahmadhini, Novi Tri; Harahap, Rika Sylvia (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Land suitability is one method used to assess the suitability of a commodity to be cultivated sustainably on land. This research aimed to highlight the issue of agricultural land for maize in Kulah Hilir District, Labuhan Batu Regency, North Sumatra. The method used in this research is the matching evaluation method (weight factor match). The data used in this research is secondary data sourced from research data in the form of rice agricultural land suitability data with the title Evaluation of Land Suitability for Rice (Oryza sativa L.) in Kualuh Hilir District, Labuhanbatu Regency. North, North Sumatra. This research showed that the land suitability class of corn in Kualuh Hilir District, North Labuhanbatu Regency, North Sumatra, using the weight factor matching method, is in class S2,